A Glimpse into Software Defined Data Center. - Fung, Han Ping (2014)
Existing data centers today are not ready to support IT organizations to meet the ever changing business demands. Therefore, next generation of data center like Software Defined Data Center (SDDC) is explored and expected to come to rescue. However, SDDC is relatively new since its inception in 2012 whereby there are different early interpretations on its definition, criteria, reference architecture and values that SDDC brings. There is also limited literature and sharing on how a SDDC works. The objective of this study is to shed some lights on SDDC operational definition, criteria, reference architecture, and depiction on how SDDC works in three scenarios as well as standardized the values it brings. Moreover, some factors to guide IT organizations on how to adopt SDDC are also discussed. This study has taken a qualitative approach in which SDDC literature is reviewed and some SDDC IT professionals are interviewed. Lastly, limitations of the study, future research and conclusion are also provided.